Keberkahan Al-Quds Perspektif Al-Quran: Keberkahan al-Aqsha Perspektif al-Quran - L, Sholehuddin (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2021)
For 15 centuries al-Quds was under the auspices of Islam al-hanif which was peaceful, prosperous and prosperous, full of blessings. Today the facts show that on the contrary, there has been a storm of humanitarian storms, full of conflict, oppression, the slaughter of millions of innocent people who died, the expulsion and seizure of the Palestinian property takes place almost every day without stopping due to the cruelty and savagery of the Zionist entity. Then where is the blessing of al-Quds? How did that tyranny continue to happen on the earth of the prophets? In order to respond to this humanitarian problem, the author tries to trace using the Research library study to reveal facts based on the approach of the letter al-Isra verse one which is correlated with similar verses and sociological-anthropological empirical data. The results of the study prove that the meaning of barakah is a gift of Allah absolutely without the involvement of creatures and the law of cause and effect (causality) from human efforts optimally. The conclusion of the study shows that the term barakah is divided into three aspects, namely: first, security from disturbance by evil humans, the wild star, as isra Rasulullah's journey from Mecca to Palestine. Second, the fertility of nature such as a variety of fruits, vegetables, livestock, grows. Third, peace, which is obtained through the serious efforts of the Muslim community as a legal provision of causality which causes peace. The factors of hard work and maximum smart work are the parameters of Allah's grace in overcoming conflicts and fighting for the liberation of al-Quds, so that blessings in the sense of peace on the earth of the martyrs can be realized.